2022
DOI: 10.3389/fonc.2022.954495
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of indoleamine 2,3-dioxygenase 1 expression in solid tumors: A systematic review and meta-analysis

Abstract: BackgroundAs an emerging immune checkpoint molecule, indoleamine 2,3-dioxygenase 1 (IDO1) is an immunosuppressive rate-limiting enzyme in metabolism of tryptophan to kynurenine. The expression of IDO1 affected the prognosis of patients in cancers by regulating the kynurenine pathway, inhibiting the proliferation of T cells. However, the association between IDO1 and solid tumor prognosis was controversial. To further investigate the role of IDO1 expression in solid tumors, we conducted the systematic review and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Addiotionally, IDO1 seems to promote epithelial-mesenchymal transition through PD-L1 pathway [ 52 ]. Zhang et al evaluated the prognostic role of IDO1 expression in solid tumors through a systematic review and meta-analysis and they found shorter Overall Survival associated with high expression of IDO1 , corroborating with our findings [ 53 ].…”
Section: Discussionsupporting
confidence: 91%
“…Addiotionally, IDO1 seems to promote epithelial-mesenchymal transition through PD-L1 pathway [ 52 ]. Zhang et al evaluated the prognostic role of IDO1 expression in solid tumors through a systematic review and meta-analysis and they found shorter Overall Survival associated with high expression of IDO1 , corroborating with our findings [ 53 ].…”
Section: Discussionsupporting
confidence: 91%
“…Accelerated tryptophan metabolism via IDO enzyme occurs in several disorders, such as neurodegeneration, cardiovascular diseases, infections and malignancies. Malignant cells can activate IDO enzyme expression [113] which is observed in many human cancers [114]. In tryptophan catabolism, the IDO enzyme has diverse biological roles in immune suppression and tumour progression [115].…”
Section: Genetics Epigenetics and Tryptophan Metabolismmentioning
confidence: 99%
“…To date, there are several inhibitors available that have already entered clinical trials [115]. A recent meta-analysis indicates that IDO expression may be a prognostic marker of cancer in various tissues and that its expression is a promising pharmaceutical target [113].…”
Section: Genetics Epigenetics and Tryptophan Metabolismmentioning
confidence: 99%
“…Kynurenine, an IDO product, activates the aryl hydrocarbon receptor (AhR), facilitating the differentiation of T cells into Tregs and contributing to immune tolerance [115]. The genetic makeup of individuals regulates IDO1 expression through the polymorphisms or mutations that regulate the IDO1 gene directly or modulate the regulatory pathways governing IDO1 expression [116][117][118]. Polymorphisms associated with heightened IDO1 activity, fostering a suppressive TME that is conductive of immune evasion [116][117][118], indicating their consideration in the therapeutic potential of IDO1-targeted interventions [119,120].…”
Section: Bcg and Chemokines Attracting Effector Versus Suppressive Po...mentioning
confidence: 99%
“…The genetic makeup of individuals regulates IDO1 expression through the polymorphisms or mutations that regulate the IDO1 gene directly or modulate the regulatory pathways governing IDO1 expression [116][117][118]. Polymorphisms associated with heightened IDO1 activity, fostering a suppressive TME that is conductive of immune evasion [116][117][118], indicating their consideration in the therapeutic potential of IDO1-targeted interventions [119,120]. Furthermore, chemotherapeutic agents can elevate IDO1 expression as a result of the cancer cell stress response [121,122].…”
Section: Bcg and Chemokines Attracting Effector Versus Suppressive Po...mentioning
confidence: 99%